2015
DOI: 10.1093/rheumatology/kev199
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel diseases in anti-neutrophil cytoplasmic antibody–associated vasculitides: 11 retrospective cases from the French Vasculitis Study Group

Abstract: Coexistence of IBD and AAV is a rare condition. The therapeutic management of these patients includes corticosteroids in all cases and immunosuppressive drugs in some patients. Coexistence of IBD and AAV might be explained by common underlying inflammatory responses and cytokine profiles polarized towards either Th1 or Th2. Finally, in the presence of digestive manifestations in the context of AAV, the hypothesis of IBD should be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…A recent genetics study showed that patients with TAK complicated with UC displayed higher positivity for HLA-B * 52:01 than patients without UC [20]. Granulomatous inflammation is a hallmark of both TAK and GPA, as is also a key feature of CD [21,22]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent genetics study showed that patients with TAK complicated with UC displayed higher positivity for HLA-B * 52:01 than patients without UC [20]. Granulomatous inflammation is a hallmark of both TAK and GPA, as is also a key feature of CD [21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients with IBD and TAK were also more likely to have constitutional symptoms, gastrointestinal symptoms, and headache/dizziness but were less likely to experience claudication of the extremities. A recent case series of 11 patients with ANCA-associated vasculitides (7 patients with GPA and CD and 4 with EGPA and UC) suggested that the coexistence of GPA and UC or EGPA and CD was infrequent [22]. We did not observe this exclusive associative pattern in our patients (1 GPA with CD, 3 GPA with UC, 1 EGPA with CD, and 1 EGPA with UC), but our study replicates another important finding—that the diagnosis of IBD most often antedates the diagnosis of ANCA-associated vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…3). The coexistence of AAV with IBD has been described in some patients, but is rare 95,96 . In this context, IBD usually precedes AAV by several years 96 .…”
Section: Recommandationmentioning
confidence: 99%
“…Similarly, there was a strong female predominance (especially in large vessel and AAV), and IBD-preceded vasculitis also in about ∼70%. Data from France confirmed these findings [10,11]. In a more general setting such as systemic lupus erythematosus, most of the GI comorbidities were found to be of the IBD type.…”
Section: Clinical Presentationmentioning
confidence: 64%